CRAFTING MEDIA TO ENHANCE STUDENTS’ ENGLISH VOCABULARY - Dira Permana; Siti Syafi'atul Qomariyah (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2018)
This study aims at (1) seeking whether or not crafting media is able to enhance students’ English vocabulary of fourth grade at SDIT Anak Sholeh Mataram and (2) elaborating on how Craftingmedia is implemented to enhance students’ English vocabulary of fourth grade at SDIT Anak Soleh Mataram. This study used Classroom Action Research (CAR) with test, observation, and documentation as the instruments of gaining data. Based on data findings, the mean score of pretest was 80.7 and posttest was 88.9. This significant gap in scores between pretest and posttest (8.2) implied there had been enhancement in students’ English vocabulary achievement as the students were taught by using Crafting media. Crafting media was implemented through several related phases which presented students’ direct and active selves-involvement to pump up the students’ learning motivation to recognize various objects their surroundings. Thus, it can be concluded that Crafting media is able to enhance students’ English vocabulary learning of fourth grade at SDIT Anak Sholeh Mataram. Furthermore, Crafting also could help the students drive their motor and language skills. Therefore, it is expected that English teachers use Crafting media as an alternative teaching media to enhance students’ vocabulary in the English class learning.